Histological Basis of Normal and Abnormal Embryonic Development: A Critical Analytical Review - Kamel, Reyim Hameid; Dakhil, Zainab Falih (American Journal of Biology and Natural Sciences, 2026)
Embryonic development is considered to be a highly intricate biological process that includes the differentiation of cells, morphogenesis of tissues, and formation of various organ systems at distinct temporal periods. Advances in stem cell-based embryo models, spatial transcriptomics, and three-dimensional organoids have significantly influenced the understanding of developmental processes in the context of histology. The present comprehensive review aims to provide an overview of the histology of normal embryonic development processes, including gametogenesis and organogenesis. In addition to that, it will provide a critical analysis of abnormal developmental processes, including teratogenesis, neural tube formation, and congenital anomalies in the context of histopathology. In accordance with recent advances in human embryo models, epigenetic reprogramming, and recent studies published during 2023–2025, this approach will contribute to the understanding of the structural basis of various physiological as well as abnormal embryonic development processes.